The role of medical conditions and primary care services in five-year substance use outcomes among chemical dependency treatment patients - Mertens, Jennifer R. (2008)
INTRODUCTION: Health problems are prevalent in chemical dependency (CD) treatment populations, and often precede reductions in substance use among untreated populations. Few studies have examined whether medical problems predict better long-term outcomes in treated individuals, or how primary care utilization and CD/primary care service integration affects long-term outcomes among those with health problems METHOD: In a sample of 598 CD patients in a private health plan, logistic regression models examined whether Substance Abuse-related Medical Conditions (SAMCs), integrated medical and CD care, and on-going primary care predicted remission of CD problems at 5 years. RESULTS: Those with SAMCs were no more likely than others to be remitted at 5 years except among young adults and those with medical, but not psychiatric SAMCs. Higher levels of medical problem severity at intake and receiving integrated CD and primary care in the index treatment episode predicted remission in the full sample and among those with SAMCs. Among those with SAMCs, individuals with ongoing medical care—two to ten primary care visits—in the 5 years following intake were more likely to be remitted at 5 years than those with fewer visits. CONCLUSIONS: This study highlights the potentially important role of medical services in the long-term treatment of CD disorders. CD treatment may benefit from a disease management approach similar to that recommended for other chronic medical problems: specialty care when the condition is severe followed by services in primary care when the condition is stabilized.